Strategies in scheduling marine protected area establishment in a network system. Issue 1 (14th December 2018) - Kininmonth, Stuart; Weeks, Rebecca; Abesamis, Rene A.; Bernardo, Lawrence Patrick C.; Beger, Maria; Treml, Eric A.; Williamson, David; Pressey, Robert L.
Abstract: Instantaneous implementation of systematic conservation plans at regional scales is rare. More typically, planned actions are applied incrementally over periods of years or decades. During protracted implementation, the character of the connected ecological system will change as a function of external anthropogenic pressures, local metapopulation processes, and environmental fluctuations. For heavily exploited systems, habitat quality will deteriorate as the plan is implemented, potentially influencing the schedule of protected area implementation necessary to achieve conservation objectives. Understanding the best strategy to adopt for applying management within a connected environment is desirable, especially given limited conservation resources. Here, we model the sequential application of no‐take marine protected areas (MPAs) in the central Philippines within a metapopulation framework, using a range of network‐based decision rules. The model was based on selecting 33 sites for protection from 101 possible sites over a 35‐yr period. The graph‐theoretic network criteria to select sites for protection included PageRank, maximum degree, closeness centrality, betweenness centrality, minimum degree, random, and historical events. We also included a dynamic strategy called colonization–extinction rate that was updated every year based on the changing capacity of each site to produce and absorb larvae. Each rule was evaluated in the context of achieving the maximum metapopulation mean lifetime at the conclusion of the implementation phase. MPAs were designated through the alteration of the extinction risk parameter. The highest ranked criteria were PageRank while the actual implementation from historical records ranked lowest. Our results indicate that protecting the sites ranked highest with regard to larval supply is likely to yield the highest benefit for fish abundance and fish metapopulation persistence. Model results highlighted the benefits of including network processes in conservation planning.